(3GdJShjb GdOhdjs - (3HOjY Lejd(B, (3bOhs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2009)
(3GdJShjb GdOhdj,fXQjGJ GdJHGOd GdJLGQj GdOhdj hCSSg,HjFI GdJShjb GdOhdj,eJZjQGJ GdHjFI GdOhdjI,HMhK GdJShjb hfXe GdeYdheGJ GdJShjbjI,JMdjd GdCShGb GdNGQLjI,GSJQGJjLjGJ GdONhd Edi GdCShGb GdOhdjI,SJQGJjLjGJ GdSdYI,SJQGJjLjGJ GdJSYjQ,SJQGJjLjGJ GdJhRjY GdOhdj,SJQGJjLjGJ GdJQhjL,JShjb GdNOeGJs
Keywords: (3GdJShjb GdOhdjs